2022
DOI: 10.5558/tfc2022-005
|View full text |Cite
|
Sign up to set email alerts
|

A review of climate change effects on the regeneration dynamics of balsam fir

Abstract: Balsam fir (Abies balsamea) is one of the most abundant softwood species in eastern Canada but is projected to be adversely affected by climate change. Balsam fir decline could occur due to a combination of reduced germination and regeneration, lower growth and competitive ability, and higher rates of mortality. However, tree regeneration represents one of the most vulnerable stages to climate-induced stress. In this paper, we synthesize potential and observed effects of climate change on balsam fir regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Nonetheless, our research indicates that the southward extent of balsam fir is not directly limited by temperature, as seedling growth increases well beyond the current average temperature of the species' southern range boundary. Recent research has also reported similar temperature-related growth benefits in young balsam fir in natural conditions (Collier et al, 2022), and no effect of winter warming on germination success (Vaughn and Taylor, 2022). Interestingly, the southward range of balsam fir saplings was observed expanding with climate warming, while mature fir migrated poleward (Boisvert-Marsh et al, 2014), suggesting that balsam fir may be more sensitive to climate stress in later stages of life.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Nonetheless, our research indicates that the southward extent of balsam fir is not directly limited by temperature, as seedling growth increases well beyond the current average temperature of the species' southern range boundary. Recent research has also reported similar temperature-related growth benefits in young balsam fir in natural conditions (Collier et al, 2022), and no effect of winter warming on germination success (Vaughn and Taylor, 2022). Interestingly, the southward range of balsam fir saplings was observed expanding with climate warming, while mature fir migrated poleward (Boisvert-Marsh et al, 2014), suggesting that balsam fir may be more sensitive to climate stress in later stages of life.…”
Section: Discussionmentioning
confidence: 75%
“…Though plagued with a risky hydraulic framework (Sperry and Tyree, 1990), shorter balsam fir have less distance to transport water therefore avoiding the risk of embolism and moisture stress that larger, mature trees face due to greater xylem tension, a higher exposure to drought conditions, and a greater moisture requirement (Sperry and Tyree, 1990;Tyree and Ewers, 1991;Domec et al, 2008;McDowell and Allen, 2015;Aubin et al, 2018;McGregor et al, 2021;Rollinson et al, 2021). The moisture dependence of balsam fir has been noted in previous studies (D 'Orangeville et al, 2013'Orangeville et al, , 2018aCollier et al, 2022), and may be explained by the growth efficiency trade-off between tracheid embolism resistance and hydraulic conductivity; in non-moisture limiting conditions, a low conductivity may reduce competitiveness (Sperry and Tyree, 1990;Tyree and Ewers, 1991;Domec et al, 2008). Therefore, the generally hydric conditions throughout the range of balsam fir promote a high-risk hydraulic framework, fast growth, and a subsequent moisture dependency, thereby potentially reducing climate resilience and competitiveness in conditions with high hydrological variability.…”
Section: Discussionmentioning
confidence: 81%
“…An experimental study by Vaughn et al ( 2021 ) found reduced mortality and sustained height growth in the context of drought for temperate‐climate‐suited Acer rubrum in comparison to colder‐climate‐adapted species such as Abies balsamea . In a synthesis of the effects of climate change on Abies balsamea regeneration, Collier et al ( 2022 ) alternatively found that the adverse impacts on Abies balsamea may occur with a complex combination of processes including reduced competitive fitness and mortality of overstory trees. The potentially extensive delay in the timing of leaf senescence found in our study for boreal species in the Acadian Forest Region suggests that future nutrient resorption success may be diminished for these species in comparison to temperate species.…”
Section: Discussionmentioning
confidence: 99%
“…Balsam fir (Abies balsamea) is a mid-to -late successional species that is adapted to cooler climates [1,2]. Balsam fir trees tend to experience optimum growth in regions with an average temperature of 2 -4°C, though they can tolerate temperatures lower than 40°C [2,3].…”
Section: Introductionmentioning
confidence: 99%